Spatial Standardization of Spect Brain Images With Perfusion Radiopharmaceuticals - Nikolay Nikolov; Sergey Makeev; Tatiana Novikova; Vladislav Tsikalo (Innovative Biosystems and Bioengineering, 2020)
Background. In the study of 3D images of the brain according to emission computed tomography (SPECT) there is a problem of their spatial orientation for the correct construction of sections and subsequent analysis of the symmetry of effective hemisphere perfusion. The brain on the original images can take virtually any orientation, resulting in asymmetry of distribution of radiopharmaceutical agents (RPA) on sections of parallel or perpendicular coordinate axes. In turn, this can lead to incorrect interpretation of clinical data.